Gut commensal Parabacteroides distasonis exerts neuroprotective effects in acute ischemic stroke with hyperuricemia via regulating gut microbiota-gut-brain axis - Hongming Wei; Lu Zhan; Xinhuang Lv; Yan Lin; Jie Zheng; Wenwen Yang; Jiaming Liu; Jing Sun; Songfang Chen (Journal of Translational Medicine)
Abstract Background Hyperuricemia is considered as an independent risk factor for acute ischemic stroke (AIS), and some AIS patients are accompanied by an increase in serum uric acid. Recent studies have highlighted the important role of gut microbiota in both hyperuricemia and AIS, but there is little available data on the relationship between gut microbiota and the pathogenesis of AIS with hyperuricemia (HAS). Methods Here we profiled the gut microbiota composition in 63 HAS patients and 269 non-HAS patients through 16s rRNA sequencing. Male rat with hyperuricemia were subjected to middle cerebral artery occlusion (MCAO) to establish HAS model and were then treated with Parabacteroides distasonis. Subsequently, the neurological deficit, pathological damages and blood-brain barrier disruption were evaluated. Moreover, the levels of ROS, inflammatory cytokines, NF-𝜿B pathway related protein, and vascular density markers were determined. Results There were significant differences of gut microbiota composition between HAS patients and non-HAS patients, and a significant decrease in the abundance of Parabacteroides in HAS patients compared to non-HAS patients. Animal experiments showed that supplementation with P. distasonis increased beneficial commensal bacteria, significantly improved neurological deficits, pathological damages and BBB disruption, as well as reduced the level of serum uric acid in HAS rats. We further demonstrated that P. distasonis treatment decreased ROS level and increased SOD2 level, thereby reducing oxidative stress. Meanwhile, P. distasonis effectively inhibited NF-𝜿B signal pathway and reduced the production of inflammatory cytokines, including TNF-α and IL-1β, alleviating the inflammatory response. Notably, P. distasonis treatment increased the levels of vascular density markers including cluster of differentiation 31 (CD31) and alpha-smooth muscle actin (α-SMA), ameliorating vascular damage in HAS rats. Conclusions Together, these findings highlighted the important role of P. distasonis in the pathogenesis of HAS, and its mechanism was involved in the regulation of gut microbiota-gut-brain axis, which implied a novel strategy against HAS.